Interventions for pre‐school children with co‐occurring phonological speech sound disorder and expressive language difficulties: A scoping review. Issue 4 (3rd April 2022) - Rodgers, Lucy; Harding, Sam; Rees, Rachel; Clarke, Michael T.
Abstract: Background: Recent evidence suggests that pre‐school children with co‐occurring phonological speech sound disorder (SSD) and expressive language difficulties are at a higher risk of ongoing communication and literacy needs in comparison with children with these difficulties in isolation. However, to date there has been no systematic or scoping review of the literature specific to interventions for children with this dual profile. Aims: To explore the evidence regarding interventions for pre‐school children with co‐occurring phonological SSD and expressive language difficulties, including the content/delivery of such interventions, areas of speech and language targeted, and a broad overview of study quality. Methods & Procedures: A scoping review methodology was used in accordance with the guidance from the Joanna Briggs Institute. Following a systematic search of Ovid Medline, Ovid Emcare, OVID Embase, CINAHL, Psychinfo and ERIC, 11 studies were included in the review. A researcher‐developed data extraction form was used to extract specific information about each intervention, with the JBI appraisal tools used to provide a broad overview of the quality of each study. Main contribution: Included papers consisted of six randomized controlled trials (RCTs), two cohort studies, two case studies and one case series. Interventions fell into two main categories: (1) integrated interventions that combined content for both speech and language targets and/or explicitly used the same type of technique to improve both domains; and (2) single‐domain interventions that explicitly included content to target speech or language only, but also aimed to improve the other domain indirectly. Study quality varied, with detail on the content, context and delivery of interventions often underspecified, hampering the replication and clinical applicability of findings. Conclusions & Implications: Early emerging evidence was identified to support both integrated speech and language interventions as well as single‐domain interventions. However, caution should be exercised due to the variation in the quality and level of detail reported for the interventions. Future intervention studies may seek to address this by reporting in accordance with Template for Intervention Description and Replication (TIDieR) reporting guidelines. This approach would enable clinicians to consider the applicability of the intervention to individual children within differing settings. What this paper adds: What is already known on the subject: Pre‐school children with co‐occurring phonological SSD and expressive language difficulties frequently present within speech and language therapy services. These children are at a higher risk of long‐term communication and literacy difficulties compared with children with these needs in isolation. Some emerging evidence suggests that interventions for children with this co‐occurring profile may exist within the literature; however, this evidence may not be known to clinicians in everyday practice. What this paper adds to existing knowledge: This review is the first to systematically examine evidence of interventions for pre‐school children with co‐occurring phonological SSD and expressive language difficulties. The review identified a small number of intervention studies that varied in research quality and level of detail provided regarding the content and delivery of interventions. What are the potential or actual clinical implications of this work?: The findings of this study highlight published evidence for interventions for pre‐school children with co‐occurring phonological SSD and expressive language difficulties. These may take the form of integrating techniques for speech/language into a single intervention, or the explicit targeting of one domain with the aim of also influencing the other. However, there is a need for further high‐quality research in this area. Such studies should provide sufficient detail to enable replication. This would enable clinicians to understand the relevance and applicability of such intervention findings to the individual children they see within their clinical practice.